The Effect of Accounting Conservatism and Cash Flow on Cash Holding with Information Asymmetry as a Moderating Variable - Fadilah, Annisa; Achyani, Fatchan (Majapahit Journal of Islamic Finance and Management, 2025)
Cash is an asset that plays an important role in the running of a company's operational activities. Cash holding is the amount of cash and cash equivalents held by a company to meet operational needs, investments, and other sudden needs. Companies usually hold cash to meet obligations, manage risks, and take advantage of investment opportunities. Cash holding is cash held by a company to meet daily activities. The purpose of this study is to analyze the effect of accounting conservatism and cash flow on cash holding with information asymmetry as a moderating variable. The type of research used is quantitative research with a non-participant observation method. The sample used in this study was 162 energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample was determined using the purposive sampling method. This study uses multiple linear regression analysis and is processed using MiniTab 19. The results of the study show that: (1) Accounting Conservatism does not have a significant effect on Cash Holding (2) Cash Flow does not have a significant effect on Cash Holding (3) Information Asymmetry has a significant effect on Cash Holding (4) Information Asymmetry does not strengthen or moderate Accounting Conservatism on Cash Holding (5) Information Asymmetry does not strengthen or moderate Cash Flow on Cash Holding.